2013
DOI: 10.1002/bjs.9169
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of hypothermic machine perfusion versus static cold storage of kidney allografts on transplant outcomes

Abstract: Data from the included studies suggest that hypothermic machine perfusion reduces delayed graft function compared with static cold storage. There was no difference in primary non-function, acute rejection, long-term renal function or patient survival. A difference in renal graft survival is uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(96 citation statements)
references
References 44 publications
5
90
0
1
Order By: Relevance
“…367 Moreover, recent RCTs have demonstrated a beneficial effect of hypothermic machine perfusion on kidneys from all donor types (donation after brain death, DCD, and donors with a high KDPI), by reducing the incidence of DGF. [368][369][370] Graft survival rates varied among the studies, but Moers et al 369 reported improved 1-year graft survival in the machineperfusion group. 368,369 A first single case report in humans performed by Hosgood et al in 2011 and a larger case series in 2013 demonstrated the feasibility of normothermic machine perfusion for the preservation of the kidney graft before transplantation.…”
Section: Prevention Of Early Ischemic Injury and Dgf In Kidney Transpmentioning
confidence: 99%
See 1 more Smart Citation
“…367 Moreover, recent RCTs have demonstrated a beneficial effect of hypothermic machine perfusion on kidneys from all donor types (donation after brain death, DCD, and donors with a high KDPI), by reducing the incidence of DGF. [368][369][370] Graft survival rates varied among the studies, but Moers et al 369 reported improved 1-year graft survival in the machineperfusion group. 368,369 A first single case report in humans performed by Hosgood et al in 2011 and a larger case series in 2013 demonstrated the feasibility of normothermic machine perfusion for the preservation of the kidney graft before transplantation.…”
Section: Prevention Of Early Ischemic Injury and Dgf In Kidney Transpmentioning
confidence: 99%
“…[368][369][370] Graft survival rates varied among the studies, but Moers et al 369 reported improved 1-year graft survival in the machineperfusion group. 368,369 A first single case report in humans performed by Hosgood et al in 2011 and a larger case series in 2013 demonstrated the feasibility of normothermic machine perfusion for the preservation of the kidney graft before transplantation. Indeed, normothermic machine perfusion may have the advantage of maintaining cellular metabolism compared with hypothermic machine perfusion and allow monitoring of viability, with the potential to increase the efficacy of drugs administered before transplantation.…”
Section: Prevention Of Early Ischemic Injury and Dgf In Kidney Transpmentioning
confidence: 99%
“…Hypothermic machine perfusion (HMP) is used with the intention to limit the occurrence of DGF and ameliorate allograft function in comparison with static cold storage (40)(41)(42). Through the continuous perfusion of the kidney with a cold preservation solution, is able to remove toxic metabolites, decrease lactic acid production and provide nutrients from the kidney.…”
Section: Perfusate Biomarkersmentioning
confidence: 99%
“…Although more updated cost-effectiveness analysis are still needed [13], current trends seem to support the use of HMP for DBD kidneys [14], especially from marginal donors [15]. Indeed, kidneys preserved on HMP show lower rates of DGF compared to cold storage and it is well recognized that DBD and ECD transplants experiencing DGF do have an increased risk of acute rejection, poor graft function, and graft failure [16].…”
Section: Journal Of Transplantation Technologies and Research Respectivmentioning
confidence: 99%